A saga da beleza: um estudo das transformações corporais na experiência travesti . - Nogueira, Francisco Jander de Sousa (2010)
This study focus on the analysis of prostituted transvestites in the city of Fortaleza Ceará. It presents personal reports about their body transformations, experience that includes a set of processes, existences and different types of relations. Contrasting identities conceptions that privilege coherence and linearity, I present trajectories and autobiographical reports contextualized by discontinuities. Having a feminine subjectivity, transvestites effectuate transformations on their physical forms, endorsed by forensic medicine or by clandestine methods. Though they opt to preserve their genitals, having a woman's body is one of their biggest goals. I understand that the use of these bodies as object of wish exposed in the "streets goes besides the discussions that permeate the travestilidade as a branded group. My approach privileges the legitimation of this practice in the perspective of the realization of wishes and the recognition of the transvestites in the condition of subjects in (trans) formation. The travestilidade is analysed based on the rituals as performance, as they consider the possibilities to survive such experience in a pleasurable way or not. In the fieldwork, I mobilized methodological tools that allowed the apprehension of peculiarities and expressivenesses concerning to the complex experience of being a woman twenty and four hours a day.